Rhizosphere Effects of Maize and Wheat Increase Soil Organic and Inorganic Carbon Release in Carbonate-Rich Soils: A Three-Source 13C Partitioning Study - Sun, Zhaoan; Zhu, Biao; Wang, Fang; He, Minyi; Meng, Fanqiao (Frontiers in Environmental Science, 2021)
In carbonate-rich soils with plants, CO2 emissions from the rhizosphere may come from as many as three sources, i.e., root-derived respiration, decomposition of soil organic carbon (SOC), and dissolution of soil inorganic carbon (SIC), so partitioning of CO2 emissions by source is important to accurately quantify the rhizosphere effect (RE). Because of limited methods for three-source partitioning of soil CO2, how living roots affect SOC and SIC release (RE) has not yet been clarified, and this urgently needs to be evaluated. In this study, the RE of summer maize and winter wheat on SOC decomposition and SIC dissolution were investigated at three phenological stages in pot experiments with the aid of 13CO2 pulse labeling combined with 13C natural abundance techniques. We found that the contribution of SIC dissolution to CO2 emissions from unplanted soils ranged from 25% to 44%. As crop growth progressed, the maize rhizosphere effect on SOC- and SIC-derived CO2 emissions increased from 14% and 74% at the elongation stage to 84% and 268% at the grain filling stage compared to that in unplanted soils, respectively, while the wheat rhizosphere effect on SOC- and SIC-derived CO2 emissions increased from 51% and 34% at the elongation stage to 77% and 76% at the grain filling stage. We concluded that the rhizosphere effects increased SOC and SIC release over the entire growing season of maize (by 54% for SOC and 159% for SIC) and wheat (by 64% and 49%) compared to that in unplanted soils, indicating that ignoring SIC dissolution in carbonate-rich soils with plants will result in overestimation of SOC decomposition.